Sweden now 1982-II - Testologen Ltd. (IMU-Testologen AB, 1986)
In this survey the questions about life style, decisional power at work and reading style have been removed.

In this survey the questions about life style, decisional power at work and reading style have been removed.
ORVESTO 1982-II
Sverige nu 1982-II
Keywords: consumption; konsumtion; newspaper readership; tidnings läsekrets; periodicals readership; tidskrifts läsekrets; shopping; shopping; retail outlets; försäljningsställen; domestic appliances; hushållsapparat; consumer goods; konsumtionsvaror; membership; medlemskap; interest (cognitive processes); intresse (kognitiva processer); Consumption and consumer behaviour; Konsumtion och konsumentbeteende; Media; Media; Public relations; Public relations; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap